2017
DOI: 10.1111/nyas.13386
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol and polydatin as modulators of Ca2+mobilization in the cardiovascular system

Abstract: In the cardiovascular system, Ca controls cardiac excitation-contraction coupling and vascular contraction and dilation. Disturbances in intracellular Ca homeostasis induce malfunctions of the cardiovascular system, including cardiac pump dysfunction, arrhythmia, remodeling, and apoptosis, as well as hypertension and impairment of vascular reactivity. Therefore, developing drugs and strategies manipulating Ca handling are highly valued in the treatment of cardiovascular disease. Resveratrol (Res) and polydatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 72 publications
0
29
0
1
Order By: Relevance
“…et Zucc, has been widely used for treatment of hyperlipemia, inflammation, infection and cancer, fever, cough, hypertension and other pharmacological benefits. Polydatin is also detected in grape, peanut, hop cones, red wines, hop pellets, cocoa-containing products, chocolate products and many daily diets [204,205]. Unlike resveratrol, which passively penetrates cells, polydatin enters cells via an active mechanism using glucose carrier and it is more resistant to enzymatic oxidation than resveratrol and possesses much better solubility in water [206].…”
Section: Polydatinmentioning
confidence: 99%
“…et Zucc, has been widely used for treatment of hyperlipemia, inflammation, infection and cancer, fever, cough, hypertension and other pharmacological benefits. Polydatin is also detected in grape, peanut, hop cones, red wines, hop pellets, cocoa-containing products, chocolate products and many daily diets [204,205]. Unlike resveratrol, which passively penetrates cells, polydatin enters cells via an active mechanism using glucose carrier and it is more resistant to enzymatic oxidation than resveratrol and possesses much better solubility in water [206].…”
Section: Polydatinmentioning
confidence: 99%
“…Studies have shown that it displays strong antioxidant, anti-inflammatory and anti-apoptotic properties. Thanks to these properties, polydatin is frequently used for treating health-related disorders such as cardiac disabilities ( 20 ), various carcinomas ( 21 , 22 ), hepatitis ( 23 ) and hepatic fibrosis ( 24 ). It can also significantly reduce lipopolysaccharide-induced lung injury ( 25 ), protect against PM2.5-induced respiratory system diseases ( 26 ) and alleviate reactive oxygen species (ROS)- and bleomycin (BLM)-induced EMT and pulmonary fibrosis ( 27 , 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…et Zucc [ 14 , 15 ]. Modern pharmacological studies have shown that polydatin regulates multiple biological activities of cardiovascular systems, including antioxidation, anti-inflammation, promotion of microcirculation, and reduction of lipid synthesis [ 15 , 16 ]. Specifically, during the period of ischemia-reperfusion, polydatin exerted a potential protective effect by either promoting autophagic flux and myocardial Ca 2+ handling [ 17 , 18 ] or regulating classic intracellular signaling including renin-angiotensin system (RAS) and the downstream Rho kinase (ROCK) pathway [ 19 ].…”
Section: Introductionmentioning
confidence: 99%